2017
DOI: 10.1177/1179551417726779
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin-Converting Enzyme Gene Polymorphisms and Nephropathy in Diabetic Patients at a Tertiary Care Centre in South India

Abstract: Background:Genetic polymorphisms of the angiotensin-renin pathway have been thought to influence the development of diabetic nephropathy. However, there are conflicting results regarding this association in previous studies on populations with varying ethnicity.Aims:Primary aim was to compare the frequency of distribution of angiotensin-converting enzyme (ACE) gene (insertion/deletion [I/D]) polymorphism in Tamilian Indian type 2 diabetic individuals with and without microalbuminuria. Secondary objective was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Recent research has been done to determine if the ACE Insertion/Deletion (I/D) polymorphism increases the likelihood that diabetic nephropathy would worsen. According to certain research done in Chinese and Indian populations, T2DM with DN is more likely to carry the ACE D allele;while other studies were conducted in Indian and Caucasian populations have found no association of either allele with the progression of nephropathy in T2DM [9,10] .…”
Section: Introductionmentioning
confidence: 95%
“…Recent research has been done to determine if the ACE Insertion/Deletion (I/D) polymorphism increases the likelihood that diabetic nephropathy would worsen. According to certain research done in Chinese and Indian populations, T2DM with DN is more likely to carry the ACE D allele;while other studies were conducted in Indian and Caucasian populations have found no association of either allele with the progression of nephropathy in T2DM [9,10] .…”
Section: Introductionmentioning
confidence: 95%
“…на примере бразильской популяции [25]. Не получено различий в распределении генотипов указанного гена у населения Южной Индии среди лиц с АУ и нормоальбуминурией [26]. С повышенным риском развития АУ установлена ассоциация полиморфизма гена AGTR1 у мужчин Дании, Финляндии, Франции и Швеции [27].…”
Section: îáñóAeäåíèåunclassified
“…The ACE gene is made up of 21 kilobases on the long arm of human chromosome 17q23 forming three possible genotypes that is to say II, ID or DD. 11 These ACE genetic mutations have been considered to be putative mediators of renal disease, 9 although some studies are quite controversial. 6,11 Some studies have demonstrated an association between ACE (angiotensin-converting enzyme) insertion/deletion (I/ D) polymorphisms and various metabolic indicators in type 2 diabetes mellitus (T2D) patients, while others found otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…11 These ACE genetic mutations have been considered to be putative mediators of renal disease, 9 although some studies are quite controversial. 6,11 Some studies have demonstrated an association between ACE (angiotensin-converting enzyme) insertion/deletion (I/ D) polymorphisms and various metabolic indicators in type 2 diabetes mellitus (T2D) patients, while others found otherwise. A study found an association between these polymorphisms with coronary heart disease and dyslipidemia in T2D patients.…”
Section: Introductionmentioning
confidence: 99%